Participação pública, Comunicação e inclusão Digital - Guzzi, Adriana de Araujo (2006)
The term public participation is used in programs, projects and initiatives of democratic State governments. The debate around what is participation is not new, but with the advent and the propagation of the communication technologies, especially Internet, new democratic possibilities have been created, since the mechanisms are able to change the way by which the public opinion consulting, and consequent1y listening to these consultations, can be treated. My inquiries come from the need of verifying how the public participation in information society occurs, considering at first the question: how and in what extent is democratic participation influenced by the use of new information and communication technologies? To c1arifysome historical processes which led to globalization phenomenon, I used, as reference, authors as Manuel Castells, Antonio Negri and Michael Hardt, Gilles Deleuze, Félix Guattari and Pierre Lévy, among others; professionals who work in mediation of the social constructionism, and algo a recent literature on the theory of formation of intelligent collectives of the communication networks, approached according to aspects of the social concepts of Mark Granovetter and Barry Wellman and algo under swann intelligence (Kerckhove). Working in the field of Digital Inc1usion in the last five years, it is from my professional experience, especially through Program Acessa SP, of São Paulo State Government, that I decided to carry this study through. In the processes of elaboration and implantation of the Program Acessa SP, varied experiences had been adding, amongst them Fala SP, a consulting project to the public which lasted three years, subject chosen for the study of case of this dissertation